PENGEMBANGAN MEDIA PEMBELAJARAN BIG BOOK DALAM MATERI BELAJAR IPAS SISWA SEKOLAH DASAR - Putri Hidayatul Isnaini; Iqnatia Alfiansyah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This development research aims to determine the effectiveness and feasibility of big book media from the develop medias. The model used in this development research is the 3-D model which consists of define, design, and develop stages. Another goal of this development research is to find out the making of big book media containing the material of the nation's cultural wealth in class IV IPAS subjects. The research subject used was class IV MI Assa`adah (MIAS) Bungah consisting of 24 students. The assessment instrument is carried out through a learner response questionnaire and validation from media, material and language experts. Based on the data analysis that has been obtained, the quality of this big book media gets an average value with a percentage of 92% from media experts and 96% from material experts so that it gets a very feasible category. Keywords: big book, IPAS, model 3-D